Changes in Carbohydrates in Nursery-Grown Grapevine Rootstocks - Uys, D. C.; Orffer, C. J. (South African Journal of Enology and Viticulture, 2017)
The utilisation and accumulation of sugar, starch and hemicellulose were studied in nursery-grown grapevine rootstocks. For an initial period lasting about 12 weeks all three components were utilised to varying degrees by the cuttings. Subsequently, starch and hemicellulose increased in the stem (original cutting) of the plant, while sugar remained low until the onset of winter. In the shoots, hemicellulose accumulation was very marked, whereas in the roots starch was the dominant carbohydrate component.